Adjusting of processes of microgemodynamics at sportsmen in the conditions of vestibular irritations - Syshko D.V (Kharkov National Pedagogical University, 2012)
The comparative analysis of the functional being of the regulator systems of microgemodynamics is conducted in a skin at the sportswomen of specialized in the running types of track-and-field before and after vestibular irritations. 10 highly skilled athletes of specialized in at run on middle and long distances are explored. It is shown, that the vestibular irritation for certain causes the changes of processes of microgemodynamics in a skin, showing up not only in the change of size of perfusion but also spectrum of components of mechanisms of adjusting. It is got, that high-frequency respiratory and pulse vibrations at sportswomen occupied considerably a less stake in a general spectrum and were 9,8% and 8,3% accordingly, that specifies on an optimum influx outflow of peripheral blood. Structure of vibrations of skin blood stream after the vestibular irritations at sportswomen, consists of increase of deposit of respiratory component from 9,8% to 11,4%, that is conditioned by the change of dynamics of vein pressure at pulmonary mechanical activity, attracting action of «respiratory pump».